1975
DOI: 10.1002/ps.2780060406
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and degradation of chlorfenvinphos, chlormephos, disulfoton, phorate and pirimiphos‐ethyl following spring and late‐summer soil application

Abstract: Granular formulations of chlorfenvinphos, chlormephos, disulfoton, phorate and pirimiphos‐ethyl were broadcast at 2 kg a.i./ha and incorporated to 100 mm into a sandy‐loam soil either in May or in September 1971. The relative persistence of their residues, including insecticidally active oxidation products, after both application dates was disulfoton > chlorfenvinphos > phorate > pirimiphos‐ethyl > chlormephos. When applied in September all the insecticides persisted for longer than when applied in May. Degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…However, the temperature at which this decrease takes place for most microbes is higher than the 35 C used in this experiment, and the optimum temperature range for growth of the most of the soil microorganisms is 25 to 35 C (Kaneko et al 1978). It has been reported that insecticides degraded faster in soil as soil temperature increased (Menzer et al 1970;Wheatly et al 1972;Suett, 1975). Miles et al (1983) reported an increase of chlorpyrifos and chlorfenvinphos In soil due to the increased production or reactivity of microbially generated enzymes with the insecticide substrate.…”
Section: Discussionmentioning
confidence: 89%
“…However, the temperature at which this decrease takes place for most microbes is higher than the 35 C used in this experiment, and the optimum temperature range for growth of the most of the soil microorganisms is 25 to 35 C (Kaneko et al 1978). It has been reported that insecticides degraded faster in soil as soil temperature increased (Menzer et al 1970;Wheatly et al 1972;Suett, 1975). Miles et al (1983) reported an increase of chlorpyrifos and chlorfenvinphos In soil due to the increased production or reactivity of microbially generated enzymes with the insecticide substrate.…”
Section: Discussionmentioning
confidence: 89%
“…This has 1980). The ephemeral nature of terbufos and phorate in soil has been well documented (Getzin and Chapman, 1960;Suett, 1975;Sellers, et al, 1976;Chapman et al, 1982a,b), and it is terbufos sulfoxide and phorate sulfone that are been true to some extent with the carbamate insecticides (Harris et al, 1984;Felsot, 1986), thiocarbamate herbicides ( Wilson, 1984; Harvey et al, 1986), and phenoxyacetic acid herbicides (Kirkland and Fryer, 1972). However, the enhanced degradation of organophosphorus insecticides in soil has usually been associated with a lesser degree of crow adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table VI, soil half-lives for chlorfenvinphos in several studies were 7, 63, and 135 days (Miles et ai, 1979;Suett, 1975;Bro-Rasmussen et al, 1970). As shown in Table VI, soil half-lives for chlorfenvinphos in several studies were 7, 63, and 135 days (Miles et ai, 1979;Suett, 1975;Bro-Rasmussen et al, 1970).…”
Section: A Fate In Soil Systemsmentioning
confidence: 94%